Spirometry Reference Equations from the HCHS/SOL (Hispanic Community Health Study/Study of Latinos) - LaVange, Lisa (Am J Respir Crit Care Med, 2017)
Rationale: Accurate reference values for spirometry are important because the results are used for diagnosing common chronic lung diseases such as asthma and chronic obstructive pulmonary disease, estimating physiologic impairment, and predicting all-cause mortality. Reference equations have been established for Mexican Americans but not for others with Hispanic/Latino backgrounds. Objectives: To develop spirometry reference equations for adult Hispanic/Latino background groups in the United States. Methods: The HCHS/SOL (Hispanic Community Health Study/Study of Latinos) recruited a population-based probability sample of 16,415 Hispanics/Latinos aged 18–74 years living in the Bronx, Chicago, Miami, and San Diego. Participants self-identified as being of Puerto Rican, Cuban, Dominican, Mexican, or Central or South American background. Spirometry was performed using standardized methods with central quality control monitoring. Spirometric measures from a subset of 6,425 never-smoking participants without respiratory symptoms or disease were modeled as a function of sex, age, height, and Hispanic/Latino background to produce background-specific reference equations for the predicted value and lower limit of normal. Measurements and Main Results: Dominican and Puerto Rican Americans had substantially lower predicted and lower limit of normal values for FVC and FEV(1) than those in other Hispanic/Latino background groups and also than Mexican American values from NHANES III (Third National Health and Nutrition Examination Survey). Conclusions: For patients of Dominican and Puerto Rican background who present with pulmonary symptoms in clinical practice, use of background-specific spirometry reference equations may provide more appropriate predicted and lower limit of normal values, enabling more accurate diagnoses of abnormality and physiologic impairment.